2021
DOI: 10.1073/pnas.2107148118
|View full text |Cite
|
Sign up to set email alerts
|

Increased in vitro neutralizing activity of SARS-CoV-2 IgA1 dimers compared to monomers and IgG

Abstract: Here, we expressed two neutralizing monoclonal antibodies (Abs) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; H4 and B38) in three formats: IgG1, IgA1 monomers (m), and IgA1 dimers (d) in glycoengineered Nicotiana benthamiana plants. All six Ab variants assembled properly and exhibited a largely homogeneous glycosylation profile. Despite modest variation in antigen binding between Ab formats, SARS-CoV-2 neutralization (NT) potency significantly increased in the following manner: IgG1 <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 13 publications
1
54
0
Order By: Relevance
“…In summary, this study demonstrates the optimal combination of CHO-K1 host cell line, expression vector, and fed-batch or continuous bioprocesses to produce the complex spike protein in large amounts at the highest quality and is already used successfully in ongoing serological studies or to develop novel anti-SARS-CoV-2 antibody formats (Garner-Spitzer et al, 2021;Kallolimath et al, 2021;Sun et al, 2021). The availability of viral proteins in high quality and sufficient amounts now allows investigating the biological and virologic basics of SARS-CoV-2 to understand the infection and propagation mechanisms, the virus distribution in the body, the docking of the virus, viral immune evasion, and the immune response mechanism of the human body in more detail.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, this study demonstrates the optimal combination of CHO-K1 host cell line, expression vector, and fed-batch or continuous bioprocesses to produce the complex spike protein in large amounts at the highest quality and is already used successfully in ongoing serological studies or to develop novel anti-SARS-CoV-2 antibody formats (Garner-Spitzer et al, 2021;Kallolimath et al, 2021;Sun et al, 2021). The availability of viral proteins in high quality and sufficient amounts now allows investigating the biological and virologic basics of SARS-CoV-2 to understand the infection and propagation mechanisms, the virus distribution in the body, the docking of the virus, viral immune evasion, and the immune response mechanism of the human body in more detail.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, one can assume that such antibodies if locally present at mucosal surfaces, particularly as dimeric IgAs, could efficiently neutralize and/or eliminate virions and therefore, potentially diminish the risk of infection by SARS-CoV-2 variants. In this regard, longer hinge region and multivalency of IgA1 antibody dimers allow enhancing SARS-CoV-2 neutralization in vitro as compared to their IgG1 counterparts (Sun et al, 2021; Wang et al, 2021b). In line with this, we found that the loss of neutralization activity of Cv2.1169 against BA.1 and BA.2 was greatly rescued by avidity effects of the antibody produced in its dimeric IgA form.…”
Section: Discussionmentioning
confidence: 99%
“…The same holds true in another in vitro setting ( Table 3 ). 124 Nevertheless, more studies are urgently required to assess the safety and therapeutic effects of IgA-enriched products in preventing SARS-CoV-2 infection.…”
Section: Therapeutic Iga Antibodies Against Sars-cov-2mentioning
confidence: 99%